Is Your Museum Grant-Ready? - Sutton, Sarah (Rowman & Littlefield Publishers, 2018)
Grant funding is a critical part of museum life, yet to many it seems mysterious. This second edition of Is Your Museum Grant-Ready? isyour guide to assessing readiness to attract grants, understanding how grant funders work, learning how to design highly-fundable projects and programs, and writing and submitting proposals. The author's tips, charts, models, and examples will help you create a manageable and rewarding grant program, or update and strengthen your present program. How can grants strengthen your institution? How do you know if your institution is ready to win grants? How do you know where to apply? What can you do to improve your chances of winning a grant? How has the world of grant funding changed? Every zoo, garden, aquarium, museum and historic site finds itself asking these questions when considering grant funding to expand or improve programs, broaden its reach, or simply maintain its existing level of performance. Here are your answers. Is Your Museum Grant-Ready? is invaluable to museums and informal learning institutions, and to students studying museum work.